Watermarking Security - Bas, Patrick; Furon, Teddy; Cayre, François; Doërr, Gwenaël; Mathon, Benjamin (SpringerBriefs in Signal Processing,, 2016)
This book explains how to measure the security of a watermarking scheme, how to design secure schemes but also how to attack popular watermarking schemes. This book gathers the most recent achievements in the field of watermarking security by considering both parts of this cat and mouse game. This book is useful to industrial practitioners who would like to increase the security of their watermarking applications and for academics to quickly master this fascinating domain.